2020
DOI: 10.3390/coatings10090878
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluorine Incorporation on DLC Films Deposited by Pulsed Cathodic Arc Deposition on Nitrile Butadiene Rubber and Polyurethane Rubber Substrates

Abstract: Diamond-like carbon (DLC) and fluorinated diamond-like carbon (F-DLC) films were deposited via pulsed cathodic arc deposition on pretreated nitrile butadiene rubber (NBR) and polyurethane (PU) rubber substrates. Both DLC and F-DLC films showed a more than 50% decrease in coefficients of friction compared to uncoated NBR and PU rubber substrates. The incorporation of fluorine was found to have little influence on the film coefficient of friction. However, a decrease in film wettability was overserved in the F-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Zhang et al [25] reviewed the effects of fluorine-doped DLC's mechanical properties and found that a change of environment, particularly moisture, does not affect the frictional behaviors of fluorinated samples. Other studies have shown similar results [26][27][28]. This mostly due to the fact that the introduction of F atoms into the films enhances the formation of CF x bonds and induces strong electronegativity on the fluorine side.…”
Section: Mechanical Propertiessupporting
confidence: 67%
“…Zhang et al [25] reviewed the effects of fluorine-doped DLC's mechanical properties and found that a change of environment, particularly moisture, does not affect the frictional behaviors of fluorinated samples. Other studies have shown similar results [26][27][28]. This mostly due to the fact that the introduction of F atoms into the films enhances the formation of CF x bonds and induces strong electronegativity on the fluorine side.…”
Section: Mechanical Propertiessupporting
confidence: 67%
“…Along with XPS, one of the indirect approaches to determine the bonding types of carbon materials is Raman spectroscopy. In general, two important peaks of G (~1550 cm − 1 ) and D (~1360 cm − 1 ) can be deconvoluted in Raman spectra of the DLC films [19,[35][36][37][38]. The D peak arises from the disordering of sp 2 carbon atoms in aromatic rings, while the G peak is allocated to the stretching of carbon-carbon bonds in aromatic rings and olefinic chains [18,39].…”
Section: Surface Chemistry Of the Filmsmentioning
confidence: 99%
“…DLC can be deposited on various types of matrix materials, such as alloys, stainless steel, glass, etc., and can provide corking mechanical protection [12][13][14]. However, there are few studies that apply it to the rubber field, and this is mainly due to the large difference in hardness between DLC and nitrile rubber (NBR) [15]. The hardness of DLC films is mostly 15-60 GPa, putting it in the category of hard films [16,17].…”
Section: Introductionmentioning
confidence: 99%